1982
DOI: 10.1093/jn/112.7.1287
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on the Development of Hypercholesterolemia in Rabbits Fed Semipurified Diets Containing Casein

Abstract: Young and adult male rabbits were alternately fed semipurified diets and a commercial diet over a period of 57 weeks. The semipurified diets, containing either casein or soy protein, and the commercial diet were fed either ad libitum or on a restricted basis. When a restricted feeding regime was applied, both in the young and adult rabbits, significantly higher levels of serum cholesterol were observed in the animals fed casein compared with their counterparts fed soy protein. However, during the first period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…A long-duration, low-cholesterol diet causes atherosclerotic lesions with smooth muscle cell penetration and cholesterol deposition, which are similar to that observed in human lesions (Kolodgie et al, 1996). In contrast, advanced atheromatic lesions are induced with casein, 0.2% cholesterol, and 19% butterfat provided for 6 months to 5 years Roach, 1974, 1976;Adams et al, 1982;West et al, 1982;Rogers and Karnovsky, 1988); some studies suggest that the formation of advanced lesions depends on the age of the animal. It was suggested that age is also a critical factor for the lesions, with 3-to 4.5-yearold rabbits exhibiting fibrotic plaques while young rabbits (4 months) do not (Spagnoli et al, 1991).…”
Section: Rabbitsmentioning
confidence: 61%
See 1 more Smart Citation
“…A long-duration, low-cholesterol diet causes atherosclerotic lesions with smooth muscle cell penetration and cholesterol deposition, which are similar to that observed in human lesions (Kolodgie et al, 1996). In contrast, advanced atheromatic lesions are induced with casein, 0.2% cholesterol, and 19% butterfat provided for 6 months to 5 years Roach, 1974, 1976;Adams et al, 1982;West et al, 1982;Rogers and Karnovsky, 1988); some studies suggest that the formation of advanced lesions depends on the age of the animal. It was suggested that age is also a critical factor for the lesions, with 3-to 4.5-yearold rabbits exhibiting fibrotic plaques while young rabbits (4 months) do not (Spagnoli et al, 1991).…”
Section: Rabbitsmentioning
confidence: 61%
“…Indeed, different amounts of cholesterol in the diet (Bocan et al, 1993;Kolodgie et al, 1996), with or without a combination of oils (Kolodgie et al, 1996;Yanni et al, 2003) and specific proteins (Kritchevsky et al, 1977;West et al, 1982;Kritchevsky, 1995), as well as various durations of experimental studies (Hunt and Duncan, 1985;Rogers and Karnovsky, 1988), have been used to cause different types of lesions in arteries. A long-duration, low-cholesterol diet causes atherosclerotic lesions with smooth muscle cell penetration and cholesterol deposition, which are similar to that observed in human lesions (Kolodgie et al, 1996).…”
Section: Rabbitsmentioning
confidence: 99%
“…It is conceivable that young , rapidly growing infants are more sensitive to the type of dietary protein than adults. The hypercholester olemic effect of casein was only observed in young growing rabbits and not in their mature counter parts (12). Indeed, Tseng et al (13) reported that the type of protein in milk formulas fed from birth had pronounced effects on serum lipids of infants in a randomized, double-blind trial (Table 1) .…”
mentioning
confidence: 99%
“…6 ) have described how differences in animal growth affect plasma cholesterol level. For this reason, the diets used in our experiment were supplemented with their corresponding limiting amino acids.…”
mentioning
confidence: 99%